‘Figures in 3D’: Digital Perspectives on Cretan Bronze Age Figurines - Morris Christine; Peatfield Alan; O’Neill Brendan (Open Archaeology, 2018)
The largest corpus of clay figurines from the Cretan Bronze Age comes from ritual mountain sites known as peak sanctuaries. In this paper, we explore how the ‛Figures in 3D’ project contributes to our understanding of these figurines, aiding in the study of the technologies of figurine construction and the typological analysis of distinctive styles. We discuss how the project has, more unexpectedly, begun to create new dialogues and opportunities for moving between the material and the digital by taking a multifaceted approach that combines the data from 3D models and 3D prints with experimental work in clay.